Metodologia nowej historii filmu - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Methodology of New Film History The article deals with the specifi city of modern historiographic methods used by film historians connected with the worldwide formation labeled New Film History that started in the mid-1980s. The main thesis focuses on notions associated with a variety of historical sources, re-visions that contradict classic film history and the importance of close-readings including the cultural contexts of the film as art, as well as a medium of audiovisual communication.